Investigation of the effects of phonons on the characteristics of semiconductor quantum dot based structures / Davoud Ghodsi Nahri - Davoud Ghodsi, Nahri (2017)
In the first part of this dissertation, a dissipative quantum dot (QD) -cavity system coupled to a longitudinal acoustic (LA) phonon reservoir is studied using a numerically exact real-time path-integral approach. Three distinct dynamical regimes of weak (WC), strong (SC), and coherent coupling (CC) are discussed and more accurate conditions identifying them are presented. Our results show that to have the CC regime, which is characterized by clear vacuum Rabi oscillation (VRO), vacuum Rabi splitting (VRS) should be larger than the sum of the widths of the corresponding peaks. In order to distinguish between contributions of population decay and impure dephasing, induced by LA phonons and the dissipations, on the quantum dynamics of the QD-cavity system, we propose a two-part phenomenological expression which fits the QD-cavity decay curves perfectly and is used to calculate the corresponding spectra. The emission rate increases from the carrier recombination rate to a maximum value, which is the mean of the QD and cavity dissipation rates, with QD-cavity coupling strength. We introduce a quantity that can be applied in determining the distinct coupling regimes; This quantity enables us to identify the onset of the SC regime as the point where the impure dephasing term begins to contribute to the central band of the spectrum significantly, as a result of the existence of VRO with a very small frequency (unclear VRO) at the corresponding decay curve. Its contribution to the width of the central band increases with the coupling strength up to the onset of the CC regime, then reduces as a result of the appearance of sidebands in the spectra. The effective population decay and impure dephasing rate contribute solely to the width—of the central and sideband peaks of the triplet spectra respectively—only beyond a very large coupling strength which is the same across the considered temperature range. In the second part, we demonstrate that all the available experimental data of temperature (T)-dependent shift of photoluminescence (PL) peak of In(Ga)As QD samiii ples can be modeled successfully by using a two-oscillator model if and only if the whole temperature interval (0–300 K) is divided into a few parts (at most four parts), depending on dispersion degree of the PL peak from a monotonic behavior. Analysis of the numerical results show that excitons mostly interact (inelastically) with acoustic (AC) or optical (OP) phonons separately. Increasing QDs uniformity, by using some improved growth techniques, results in decreasing or removing the sigmoidal behavior, enhancing total AC phonon contribution to the redshift of the PL peak. Elevation of the zero bandgap (ZBG) energy up to a critical value about 1.4 eV, for In(Ga)As QDs grown using molecularbeam epitaxy, results in enhancement of QD symmetry and total OP phonon contribution and reduction of QDs uniformity and total AC phonon contribution, while a rollover happens for further increase of the ZBG. Therefore we find that the highest QD symmetry and the lowest exciton fine structure splitting correspond to this critical value of ZBG, in accordance with previous experimental results.